PENGARUH KUALITAS KEHIDUPAN KERJA (QUALITY OF WORK LIFE) TERHADAP KOMITMEN PEGAWAI PADA DINAS PENDAPATAN DAERAH KOTA PONTIANAK - B31111106, MARSIANA IRAWATI (Jurnal Manajemen Update, 2016)
Fulfillment of a good quality of work life and assured the employees can fosters they commitment to stay and work in the achievement of an organization as a workplace. The commitment of employees who grow up feeling love for the organization (affective commitment) can also be a boost to get a working life that is safe and secure in condition on continuance basis (continuance commitment). Employees commitment is certainly not just based on the fulfillment of a good working life or higher to survive, but also because of the values and norms they are as an employee or worker to contribute and accomplishments (normative commitment). This study aims to determine the effect of quality of work lifeÂ  to the employees' commitment on Dinas Pendapatan Daerah Kota Pontianak. Data was collected by distributing questionnaires to 55 employees at the Dinas Pendapatan Daerah Kota Pontianak. Analysis technique that used on this reserach is a Partial Least Square analyze through the SmartPLS software. The results showed that the quality of work life in a positive and significant impact on employee commitment. This is evidenced by value t-count larger than t-table (1.96) that is equal to 464.377. Keywords: Quality of Work Life, Employees Commitment